Problem Of Ensuring Gender Equality In The International Relations System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the second half of the XX-early XXI centuries, theoretical approaches to the status of men and women in the system of international relations began to appear in the article, which rejected tradition. The fact that stereotypes of the "policy for men, and family and children – for women" lose their relevance in connection with the social changes that are manifested in practice, economic, political, social issues facing humanity, problems of ensuring peace, stability and equal security for all and that women are equally affected as men, in this matter, the recognition of human rights. At the same time, views on issues such as the fact that gender equality is considered an integral part of sustainable development are being discussed today, and research on gender equality, the development of evidence-based proposals and recommendations aimed at equalizing the social and political rights of men and women are of particular importance.